The househusband phenomenon a study on the level of self-esteem among selected househusbands and working husbands of Tacloban City - Bacong, April Abegail C. (April Abegail Bacong, 2011)
This study is about the househusband phenomenon and the Level of self-esteem among househusbands and working husbands of Tacloban City. The study focused on five randomly selected and some of the most populated barangays of Tacloban City namely, Brgy. Diit, Brgy. Apitong, Brgy. Utap, Brgy. Calanipawan, and Brgy. Anibong. The respondents were purposely selected seventeen (17) househusbands who have been unemployed for 0-24 months, another seventeen (17) househusbands who have been unemployed for 25 months and above, gathering a total of thirty-four (34) househusbands within the identified barangays, as well as another seventeen (17) identified working husbands of Tacloban City. All in all, the researchers made use of 51 respondents to fit the requirements of the research design concerning the analysis of variance. It was found out that the common reason why these househusbands were unemployed was mainly due to unforeseen economic factors. Also, majority of the respondents (67%) have experienced certain positive personal and emotional effects of being a househusband, and that they basically have positive social relationships with their wives, children and peers. All of the respondents' level of self-esteem was gauged using the Rosenberg Self-Esteem Scale and the Self-Esteem Mean. Through ANOVA, the null hypothesis was rejected in lieu of the alternative hypothesis, which means that there is a significant difference between their levels of self-esteem. For the Rosengerg Self-Esteem Scale, an f obs of 6.86 was found, which is greater than the value of F at a .05 level of significance which was found to be around 3.19. For the Self-Esteem Mean, an f obs of 10.05 was found, which is greater than the value of F at a .05 level of significance which was found to be around 3.15. This implies that for the two tests on self-esteem, those who have been unemployed for a short period of time have a comparatively higher level of self-esteem compared to those who have been unemployed longer. Still, the data shows that working husbands have the highest level of self-esteem among the three groups of respondents.